Application of Drip Irrigation System on Vanilla Cultivation - Nadzirah, Rufiani; Mas'udi, Ach. Fauzan Mas'udi; Indarto, Indarto; Ernanda, Heru; Joan Pamungkas, Ivo (Universitas Ahmad Dahlan, 2023)
Background: The research in Jogoyudan Village, Lumajang District, identifies a significant gap in community income, land utilization, and entrepreneurial skill development, which is addressed through a community empowerment program focusing on vanilla cultivation training. The primary research gap highlighted is the low community income, underutilized yard spaces, and inadequate training and workshops to improve entrepreneurship skills among residents. These challenges are critical in a community where agriculture is dominant but lacks diversification and modern cultivation techniques. Contribution: This community service aims to improve knowledge of cultivating vanilla and making drip irrigation. Through this activity, it is hoped that the community will get additional income from the vanilla cultivation business. Method: This study includes pre-training, training, and post-training. The training employs socialization regarding vanilla cultivation techniques and drip irrigation. The next step is the direct practice of planting and pollinating vanilla as well as the practice of assembling drip irrigation. In this activity, 25 people were selected as training participants. Results: This service program shows increased knowledge of vanilla cultivation and drip irrigation by 38%. Conclusion: The training participants can independently cultivate vanilla and create drip irrigation in the yard. This activity received an excellent response from the training participants regarding facilitators, facilities, presenters, and. Participants were very enthusiastic and enthusiastic about cultivating vanilla in their yards